Forecasting Excess Returns and Abnormal Trading Volume using Investor Sentiment: Evidence from Chinese Stock Index Futures Market. Issue 3 (19th February 2020) - Gao, Bin; Xie, Jun
ABSTRACT: We examine the ability of investor sentiment to forecast excess returns and abnormal trading volumes in Chinese stock index futures market. Based on prior research on investor sentiment, we expect investor sentiment to forecast excess returns and abnormal trading volumes, and also expect that highly volatile sentiment period and low margin requirement period will be more sensitive to investor sentiment than lowly volatile sentiment period and high margin requirement period. In a sample of CSI 300 index futures over the period 2010–2014, we find that, over a daily horizon, stock index futures sentiment reliably predicts excess returns and abnormal trading volumes, and that the sensitivity of returns and trading volumes to sentiment is more significantly positively related to the highly volatile sentiment period and low margin requirement period. Moreover, we run a VAR model and analyze the Granger causality of the system. We also find the ability of investor sentiment to cause the change of excess returns and abnormal trading volume in the daily horizon.